The complete mitochondrial genome sequences of potato (Solanum tuberosum L., Solanaceae). Issue 2 (12th December 2017) - Cho, Kwang-Soo; Cho, Ji-Hong; Im, Ju-Sung; Choi, Jang-Gyu; Park, Young-Eun; Hong, Su-Young; Kwon, Min; Kang, Jin-Ho; Park, Tae-Ho
Abstract: Potato ( Solanum tuberosum ) from the Solanaceae is the fourth most important food crop worldwide. In this study, five complete mitochondrial genome sequences of S. tuberosum were characterized through de novo assembly of whole genome sequencing data. The resulting circular mitochondrial DNA molecules ranged from 49, 171 bp to 297, 014 bp in size and contained a total of 80 non-redundant genes, comprising 34 protein-coding genes, 24 hypothetical open reading frames, 19 tRNA genes, and 3 rRNA genes. Phylogenetic analysis using common protein-coding sequences confirmed that S. tuberosum belongs to the Solanoideae subfamily in the Solanaceae family.